Die fossile Burggrabenhöhle und ihr Aragonitvorkommen auf dem Wolfstein, Neumarkt in der Oberpfalz, Bayern - Leja, Ferdinand; Knolle, Friedhart; López Correa, Matthias (Mitteilungen des Verbandes der Deutschen Höhlen- und Karstforscher, 2024)
Archaeological examinations of the castle Wolfstein above the village Neumarkt in der Oberpfalz in Bavaria (Germany) led to the rediscovery of Europe’s largest aragonite deposit within the sediment-filled cave ruin Burggrabenhöhle. The massive aragonitic speleothems had been used in large quantities to build the castle walls. This peculiar deposit was examined and presented to the public in an exhibition.
CRIS-Team Scopus Importer:2025-02-04